Biochemical responses of painted spiny lobster Panulirus versicolor fed with molluscs meal and fish meal - Kurnia, Agus; Hamzah, Muhaimin; Idris, Muhammad; Muskita, Wellem Henrik; Abidin, La Ode Baytul; Sabilu, Kadir; Yusnaini, Yusnaini; Balubi, Abdul Muis; La Usaha, La Usaha; Fatmawati, Famawati; Razak, La Ode Abdul; Khairunnisa, Khairunnisa (Syiah Kuala University, 2024)
Molluscs are one of the most preferred ingredients for marine lobster feed because the mollusc has a higher protein content. Therefore, this material has the potential to substitute the fish meals and reduce the cost for feeding lobsters. The objective of the present study was to investigate digestive enzyme activities and growth performance of painted spiny lobsters fed with a combination of mollusc meal and fish meal in the diet. Four experimental diets were formulated to contain 20% sardine fish meal and 20% mackerel fish meal (Diet A). 10% Telescopium muscle meal (TMM) + 15% golden snail meal (GSM) + 15% scallops muscle meal (SMM) (Diet B). 15% TMM + 10% GSM + 15% SMM (Diet C) and 15% TMM + 15% GSM + 10% SMM (Diet D). A total of 24 juvenile painted spiny lobsters were distributed into twelve plastic tanks (two lobsters/tank) with a size of 60 45 60 cm and reared in a recirculating system for a 50-day rearing period. The lobster was fed only one time a day (05:00 pm) with a dosage of 3% biomass weight. The results showed that the enzyme activities of lobsters fed with combined mollusc meals were higher than the enzyme activity in the lobsters fed with the fish meal combination diet. The weight gain of the painted spiny lobster fed with mollusc meal was higher than the lobster fed with a fish meal diet. Based on results of enzyme activities and growth performance. It was concluded that the combination of mollusc meal in the formulated diet was more suitable than the combination of fish meal for optimum enzyme activities and growth performance of painted spiny lobster